The Use of Technology-Based Formative Assessment in Improving Mathematics Achievement of Elementary School Students - Rasmini, Ni Wayan; Antara, Putu Aditya; Wulandari, I Gusti Ayu Agung Manik (Universitas Pendidikan Ganesha, 2023)
Mathematics achievement can be considered low among elementary school students. Formative assessments allow educators to understand where students are in their learning process. This research will analyze the use of technology-based formative assessments that can help overcome several problems in elementary schools, especially in improving student mathematics achievement. This type of research is quantitative research that uses a quasi-experimental design. The research sample will consist of elementary school students divided into two groups: an experimental group that receives a technology-based formative assessment. In contrast, the other group will be a control group that receives a traditional formative assessment. The data collection instrument consists of a pretest and post-test mathematics test. Data analysis will use statistical software such as SPSS with the t-test. This research concludes that using technology-based formative assessment significantly positively influences elementary school students' mathematics achievement. The implications of this research can help design better learning strategies for mathematics subjects in the future.